2021
DOI: 10.5090/kjtcs.20.123
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cumulative Fluid Balance and Outcomes in Acute Respiratory Distress Syndrome Patients Treated with Extracorporeal Membrane Oxygenation

Abstract: Background Extracorporeal membrane oxygenation (ECMO) has become increasingly accepted as a life-saving procedure for patients with severe acute respiratory distress syndrome (ARDS). This study investigated the relationship between cumulative fluid balance (CFB) and outcomes in adult ARDS patients treated with ECMO. Methods We retrospectively analyzed the data of adult ARDS patients who received ECMO between December 2009 and December 2019 at Korea University Anam Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Fluid balance is associated with the outcome of patients on ECMO. Lee et al ( 28 ) reported that a higher positive cumulative fluid balance on Day 3 of ECMO was associated with increased 28-day mortality. In the present study, daily fluid balance during the first 3 days of ECMO support was significantly correlated to LUS score, and LUS score ≥ 24 after 72 h ECMO support was associated with a worse outcome in patients with pARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid balance is associated with the outcome of patients on ECMO. Lee et al ( 28 ) reported that a higher positive cumulative fluid balance on Day 3 of ECMO was associated with increased 28-day mortality. In the present study, daily fluid balance during the first 3 days of ECMO support was significantly correlated to LUS score, and LUS score ≥ 24 after 72 h ECMO support was associated with a worse outcome in patients with pARDS.…”
Section: Discussionmentioning
confidence: 99%
“…For the most severe cases, veno-venous extracorporeal membrane oxygenation (V-V ECMO) has been proposed as an alternative therapeutic strategy that might reduce mortality [3][4][5]. A restrictive fluid management is recommended in patients with ARDS managed with V-V ECMO [6,7] because an excessive positive fluid balance increases mortality [8]. Transpulmonary thermodilution (TPTD) allows us to quantify pulmonary edema from the measurement of the extravascular lung water index (EVLWI) and for continuous monitoring of cardiac preload parameters such as the intrathoracic blood volume index (ITBVI) [9][10][11], which is mathematically derived from the global end-diastolic volume index (GEDVI).…”
Section: Tptd Transpulmonary Thermodilution V-v Ecmo Veno-venous Extr...mentioning
confidence: 99%